Risk Factors and the Level of Depression in Mild Coronavirus Disease 2019 (COVID-19) Patients Hospitalized at the COVID-19 Hospital Kemayoran Athletes Village, Jakarta, Indonesia - Sofiansyah, Muhammad; Samoedro, Erlang; Sugihen, Tribowo Tuahta Ginting; Siahaan, Geby Thioma Elizabeth; Setia, Yosua Hendrata Liman (Budapest International Research and Critics University, 2021)
Background: Indonesia have documented more than 400.000 Covid-19 Cases. Stigma lead Covid-19 patients to experiences depression. Suicide cases are documented at the Covid-19 Emergency Management Hospital Wisma Atlet Kemayoran Jakarta (EMHWAKJ). Goal: To determine the prevalence of depression, risk factors for depression and to see the relationship between length of stay, age and level of education with the incidence of depression in Covid-19 patients treated at EMHWAKJ.Method: Analytical descriptive with a cross-sectional approach to mild COVID-19 patients treated at EMHWAKJ. Researchers conducted interviews with MINI, Hamilton and Holmes Rahe questionnaires to 108 patients who had been screened using inclusion and exclusion criteria.Results: Depression occurred in 9 patients (8.3%). The level of depression was mild in 4 patients (44.4%), moderate in 2 patients (22.2%), severe in 1 patient (11.1%) and very severe in 2 patients (22.2%). Multiple linear regression test showed no significant correlation between length of stay and education. Age is significant correlation (p-value = 0.042) with the incidence of depression.Conclusion: There was no significant correlation between length of stay, age and education level with the incidence of depression, age had a significant correlation with the incidence of depression.